2016
DOI: 10.7150/thno.14514
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus-Targeted Theranostic Microbubbles: A New Technology towards Concurrent Rapid Ultrasound Diagnosis and Bleeding-free Fibrinolytic Treatment of Thrombosis

Abstract: Rationale: Myocardial infarction and stroke are leading causes of morbidity/mortality. The typical underlying pathology is the formation of thrombi/emboli and subsequent vessel occlusion. Systemically administered fibrinolytic drugs are the most effective pharmacological therapy. However, bleeding complications are relatively common and this risk as such limits their broader use. Furthermore, a rapid non-invasive imaging technology is not available. Thereby, many thrombotic events are missed or only diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 51 publications
1
95
0
Order By: Relevance
“…The in vitro binding assays performed on recombinant P-selectin confirmed that fucoidan could efficiently recognize and bind P-selectin, even when incorporated in the polysaccharide shell (Figure 3). Interestingly, this experiment showed that the affinity of Fuco-NPs for P-selectin was observed both at low shear stress (6.75 dyne/cm 2 ) and at high shear stress (67.5 dyne/cm 2 ), whereas most in vitro affinity assays described in the literature are performed in static conditions [21,24] or at very low (<6.75 dyne/cm 2 ) or uncontrolled shear stress [50,51].…”
Section: Discussionmentioning
confidence: 89%
“…The in vitro binding assays performed on recombinant P-selectin confirmed that fucoidan could efficiently recognize and bind P-selectin, even when incorporated in the polysaccharide shell (Figure 3). Interestingly, this experiment showed that the affinity of Fuco-NPs for P-selectin was observed both at low shear stress (6.75 dyne/cm 2 ) and at high shear stress (67.5 dyne/cm 2 ), whereas most in vitro affinity assays described in the literature are performed in static conditions [21,24] or at very low (<6.75 dyne/cm 2 ) or uncontrolled shear stress [50,51].…”
Section: Discussionmentioning
confidence: 89%
“…98,99 In addition to imaging, microbubbles offer a theranostic component to the treatment of thrombus through mechanical disruption by particle cavitation and local release of fibrinolytic agents. 100,101 …”
Section: Alternative Modalities For Molecular Imaging Of Thrombusmentioning
confidence: 99%
“…Thrombosis is developed through blood vessel wall damage or through a pathological process that induces activation of coagulation factor to cause accumulation of platelets and fibrin . Although many imaging strategies—including magnetic resonance imaging (MRI), ultrasound, computed tomography (CT), etc.—for visualization of the thrombus formation process have been developed, the specific detection and rapid evaluation of thrombotic events, especially at the molecular level, still presents a major clinical challenge. Ultrasound is a clinical diagnostic imaging modality that is widely available, portable, and non‐invasive for visualizing anatomy and physiology .…”
Section: Methodsmentioning
confidence: 99%